Descriptions of the Forests of Slavonia in Travelogues of the Early Modern Age - Skenderović, Robert (Historical Studies on Central Europe, 2022)
Forest history is a relatively new discipline in Croatian historiography. The scale of exploitation remains the main point of interest for scholars dealing with forest history. Nevertheless, recent scholarship has turned scholarly interest towards another question: Can exploitation (timber consumption) be the only criterion for the anthropization of forests? The present paper analyzes three travelogues from the seventeenth and eighteenth centuries and compares them with quantitative data originating from various historical sources. It shows how travelogues do not only offer a vivid description of a land and its inhabitants but can also be used as a valuable confirmation of historical conclusions based on quantitative historical data. Even more, travelogues may provide some specific data not available elsewhere. In this case, three travelogues (Atanazije Jurjević, Osman Aga of Timişoara/Temesvár, and Friedrich Wilhelm von Taube) give a broader understanding of the anthropization of forests in Slavonia during the early modern period.